Low and high dose methamphetamine differentially regulate synaptic structural plasticity in cortex and hippocampus - Ding, Jiuyang; Huang, Jian; Tang, Xiang; Shen, Lingyi; Hu, Shanshan; He, Jiaojiao; Liu, Ting; Yu, Zhixing; Liu, Yubo; Wang, Qiyan; Wang, Jiawen; Zhao, Na; et al. (Frontiers in Cellular Neuroscience, 2022)
Psychostimulants, such as methamphetamine (METH) can induce structural remodeling of synapses by remodeling presynaptic and postsynaptic morphology. Escalating or long-lasting high dose METH accounts for neurodegeneration by targeting multiple neurotransmitters. However, the effects of low dose METH on synaptic structure and the modulation mechanism remain elusive. This study aims to assess the effects of low dose (2 mg/kg) and high dose (10 mg/kg) of METH on synaptic structure alternation in hippocampus and prefrontal cortex (PFC) and to reveal the underlying mechanism involved in the process. Low dose METH promoted spine formation, synaptic number increase, post-synaptic density length elongation, and memory function. High dose of METH induced synaptic degeneration, neuronal number loss and memory impairment. Moreover, high dose, but not low dose, of METH caused gliosis in PFC and hippocampus. Mechanism-wise, low dose METH inactivated ras-related C3 botulinum toxin substrate 1 (Rac1) and activated cell division control protein 42 homolog (Cdc42); whereas high dose METH inactivated Cdc42 and activated Rac1. We provided evidence that low and high doses of METH differentially regulate synaptic plasticity through modulating Rac1 and Cdc42 signaling.